Investigating a potential difference between EFL teachers’ teaching strategies and learners’ learning styles - Teshager, Tigabu (Ethiopian Journal of Language, Culture and Communication, 2024)
<main class="pkp_structure_main col-xs-12" role="main"> The present study was conducted to examine a possible difference between EFL teachers’ teaching strategies and students’ learning styles at Aferewanat Preparatory and Secondary School in South Gondar. Descriptive research design was mainly used to assess the teaching strategies of five EFL teachers and the learning styles of 170 grades 11 and 12 students. Simple random sampling was used to select the students, while availability sampling was employed for teachers. Data were collected through questionnaire, classroom observations and in-depth interview. Independent sample T-test and frequency counts were used to analyze the quantitative data. On the other hand, thematic narration and description of the respondents’ ideas were used to analyse the qualitative data. The finding of the study showed that visual style was the learning style of the majority of students. In addition, note & lecture, pair work and group discussion were the most dominant teaching strategies used by teachers. Besides, there was no statistically significant difference between the teachers’ visual and auditory-oriented teaching strategies and students’ visual and auditory style categories. However, there was statistically significant difference between kinaesthetic type of teaching strategies and kinaesthetic learning styles. Hence, it’s recommended that teachers should vary their teaching strategies in line with the visual, auditory and kinaesthetic (VAK) modalities in order to meet the learning styles of their students. </main>